2021
DOI: 10.48550/arxiv.2103.11898
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Maximising line subgraphs of diameter at most $t$

Abstract: We wish to bring attention to a natural but slightly hidden problem, posed by Erdős and Nešetřil in the late 1980s, an edge version of the degree-diameter problem. Our main result is that, for any graph of maximum degree ∆ with more than 1.5∆ t edges, its line graph must have diameter larger than t. In the case where the graph contains no cycle of length 2t + 1, we can improve the bound on the number of edges to one that is exact for t ∈ {1, 2, 3, 4, 6}. In the case ∆ = 3 and t = 3, we obtain an exact bound. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…Chung, Gyárfás, Tuza, and Trotter exactly determined h 2 (∆); it is 5 4 ∆ 2 +1 when ∆ is even and slightly smaller when ∆ is odd (see the start of Section 4.1). For larger k, Cambie, Cames van Batenburg, de Joannis de Verclos, and Kang [44] showed that ω k (L(G)) ⩽ 3 2 ∆ k . In particular, h k (∆) ⩽ 3 2 ∆ k + 1.…”
Section: Higher Powersmentioning
confidence: 99%
“…Chung, Gyárfás, Tuza, and Trotter exactly determined h 2 (∆); it is 5 4 ∆ 2 +1 when ∆ is even and slightly smaller when ∆ is odd (see the start of Section 4.1). For larger k, Cambie, Cames van Batenburg, de Joannis de Verclos, and Kang [44] showed that ω k (L(G)) ⩽ 3 2 ∆ k . In particular, h k (∆) ⩽ 3 2 ∆ k + 1.…”
Section: Higher Powersmentioning
confidence: 99%